2013
DOI: 10.1158/1078-0432.ccr-12-1050
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine Kinase 1 Overexpression Contributes to Cetuximab Resistance in Human Colorectal Cancer Models

Abstract: Purpose: Although the anti-EGF receptor (EGFR) monoclonal antibody cetuximab is an effective strategy in colorectal cancer therapy, its clinical use is limited by intrinsic or acquired resistance. Alterations in the "sphingolipid rheostat"-the balance between the proapoptotic molecule ceramide and the mitogenic factor sphingosine-1-phosphate (S1P)-due to sphingosine kinase 1 (SphK1) overactivation have been involved in resistance to anticancer-targeted agents. Moreover, cross-talks between SphK1 and EGFR-depen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
94
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 41 publications
1
94
0
Order By: Relevance
“…The KRAS-mutated status is a very high prevalent alteration in mCRC that determines resistance to the monoclonal antibody cetuximab. Interestingly, it has recently reported that FTY720 could resensitize colorectal cancer cells to cetuximab, indicating a potential therapeutic relevance for FTY720 in mCRC (38). Of importance, when we stratify our series by the KRAS mutation status, the SET prognostic impact was particularly strong in those patients with KRAS-mutated (P < 0.001; Supplementary Fig.…”
Section: Discussionmentioning
confidence: 86%
“…The KRAS-mutated status is a very high prevalent alteration in mCRC that determines resistance to the monoclonal antibody cetuximab. Interestingly, it has recently reported that FTY720 could resensitize colorectal cancer cells to cetuximab, indicating a potential therapeutic relevance for FTY720 in mCRC (38). Of importance, when we stratify our series by the KRAS mutation status, the SET prognostic impact was particularly strong in those patients with KRAS-mutated (P < 0.001; Supplementary Fig.…”
Section: Discussionmentioning
confidence: 86%
“…The growth of MDA-MB-468 xenograft tumors was shown to be inhibited by ABC294640, an SphK2-specific inhibitor, when used as a single-line agent (45). Acquired resistance to chemotherapeutic drugs, hormonal therapies, and growth factor receptor inhibitors, including EGFR inhibitors, has been linked with overexpression of SphK1 in a number of malignancies (46)(47)(48)(49)(50), providing a clear rationale for the use of SphK1 inhibitors in the clinic as adjuvant therapies. Our study has shown potent antiproliferative effects of dual inhibition of EGFR and SphK1 in cell lines representing a subset of breast cancers for which there is currently a paucity of treatments, and has demonstrated in a preclinical study proof-of-principle that this combination has therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies shed further insight into the mode of action of FTY720 by demonstrating that it directly inhibits SphK1 activity both in vitro and in vivo. For instance, FTY720 could resensitize human colorectal cancer to cetuximab by inhibiting SphK1 both in vitro and in vivo, with inhibition of tumor growth, interference with signal transduction, induction of cancer cell apoptosis, and prolongation of mouse survival (91). In addition to directly inhibiting SphK1 activity, FTY720 has been demonstrated to induce SphK1 degradation via ubiquitination and subsequent proteasomal processing (93); however, the precise mechanism has not been defined.…”
Section: Sphingosine Kinase (Sphk)mentioning
confidence: 99%